The librarian's guide to homeschooling resources - Scheps, Susan G. (American Library Association, 1998)
"Serving homeschoolers begins with anticipating their needs. The Librarian's Guide to Homeschooling Resources will prepare you for homeschooler visits with: tips on serving homeschoolers (and traps to avoid); sources for legal information and educational standards homeschoolers often seek from libraries; descriptions and contact information for programs and services offered by selected public libraries; a detailed directory of state, regional, and national homeschooling organizations in the United States and Canada; and lists of correspondence schools, publishers and distributors of homeschooling materials, and resources on the Web."--Jacket